Report on National Rural Energy Planning Exercise - Planning Commission (Planning Commission, 1985)
Energy is the basis of economic development. During the Sixth Plan, a major programme was mounted for augmenting energy supply in the country. This included programmes for large scale power production, oil exploration and refining, coal production and a new programme for developing and utilising renewable sources of energy. The outlay on the energy sector comes to more than 40% of the total plan outlay.
Planning Commission Government of India
Planning Commission Government of India